Motivational cues predict the defensive system in team handball: A model based on regulatory focus theory - Debanne, T.; Laffaye, G. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study was based on the naturalistic decision-making paradigm and regulatory focus theory. Its aim was to model coaches' decision-making processes for handball teams' defensive systems based on relevant cues of the reward structure, and to determine the weight of each of these cues. We collected raw data by video-recording 41 games that were selected using a simple random method. We considered the defensive strategy (DEF: aligned or staged) to be the dependent variable, and the three independent variables were (a) numerical difference between the teams; (b) score difference between the teams; and (c) game periods. We used a logistic regression design (logit model) and a multivariate logistic model to explain the link between DEF and the three category independent variables. Each factor was weighted differently during the decision-making process to select the defensive system, and combining these variables increased the impact on this process; for instance, a staged defense is 43 times more likely to be chosen during the final period in an unfavorable situation and in a man advantage. Finally, this shows that the coach's decision-making process could be based on a simple match or could require a diagnosis of the situation based on the relevant cues.